Currency Returns and Investment Portfolio Impact in Optimizing Assets Risk - Rubiyoso, Dimas Satrio; Nugroho, Anggoro Budi (Journal of Business and Management, 2014)
This method determines the proportion of each asset to be invested based on the risk-adjusted return. To know the performance of optimal portfolios that have been formed, the writer used the Sharpe ratio and then compared with performance market of the Jakarta Composite Index (JCI). The sample data used by the author is Indonesia financial instruments which areÂ  10 stocks that listed on the LQ-45 index and the Indonesian retail bonds (ORI), and foreign currencies against rupiah that recorded as hard currency, during the observation period October 2012 to May 2014, which was determined by purposive sampling method. The results of this study, foreign currency has given advantage to the investment on financial asset instrument. It can drive the performance portfolio that consist only stock and bond from 0.0736 to 0.1103. With adding foreign currency, rate of return portfolio became 0.0554% at risk level 0.3443%. EUR (euro) and CNY (yuan) are the most affect to the portfolio performance with 23.36% and 13.36% proportion in portfolio. Based on the calculation Sharpe ratio, performance of the optimal portfolio with foreign currency, have an average better performance than the performance on JCI.Keywords: Investment, Portfolio, Foreign Currency, Risk and Return, Markowitz Efficient Theory.